Building Competitive Advantage Through Strategic Management Practices: A Qualitative Study of Service Firms - Abd. Hakam; Zainul Ulum (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
Building competitive advantage has become a critical objective for service firms operating in highly competitive and dynamic markets. Strategic management practices play a significant role in enabling organizations to align internal capabilities with external opportunities in order to sustain long-term performance. This study aims to explore how competitive advantage is developed through strategic management practices within a service firm, focusing on PT. Megah Sarana Gumilang, an outsourcing company based in Surabaya, Indonesia. The research employed a qualitative case study approach to gain an in-depth understanding of managerial strategies and organizational practices implemented by the company. Data were collected through in-depth interviews with company managers and operational staff, supported by field observations and document analysis. The collected data were analyzed using an interactive qualitative analysis model consisting of data condensation, data display, and conclusion drawing. The findings reveal that competitive advantage in the company is primarily built through the integration of human resource quality, responsive service delivery, and strong client relationship management. The organization emphasizes workforce discipline, service reliability, and continuous performance monitoring to maintain client trust and service quality. The study contributes to the strategic management literature by highlighting the importance of intangible organizational capabilities—such as service responsiveness and human capital management—in shaping competitive advantage in labor-intensive service industries. Practically, the findings provide insights for managers in outsourcing and other service sectors to strengthen strategic management practices that support sustainable organizational competitiveness.